Use and abuse of medication during 2014 FIFA World Cup Brazil: a retrospective survey. Issue 9 (10th September 2015) - Vaso, Martin; Weber, Alexis; Tscholl, Philippe M; Junge, Astrid; Dvorak, Jiri
Abstract : Objective: To examine the use of medication of top-level male players during the 2014 FIFA World Cup Brazil. Design: Retrospective survey. Participants/information: 736 top level players. Setting: The teams' physicians disclosed a list of the medications used by each player within 72 h before each match of the 2014 FIFA World Cup Brazil. Outcome measures: Average number of medications used per player per match or during the tournament; average number and percentage of players using at least one medication per match or during the tournament. Results: 67.0% of all players took various types of medication during the tournament. The most used medications during the tournament were non-steroidal anti-inflammatory drugs (NSAIDs), by 54.2% of all players, followed by analgaesics (12.6%); β-2 agonists were only used by 0.5%. On average, 0.8 medications per player were used before each match. More players were reported taking medications during the knockout round than during the qualification round (0.36±0.48 vs 0.49±0.50, p<0.001). Players from the South American and Asian Confederations took twice as many medications per match as players from the African Confederation (1.17±1.55 and 1.01±1.26 vs 0.48±0.69, both p<0.001). Conclusions: There was high use of NSAIDs during the 2014 FIFA World Cup. Although the intake of NSAIDs per match (0.35±0.46 vs 0.31±0.48, p<0.01) in the 2014 FIFA World Cup decreased compared to the 2010 FIFA World Cup, the average use was still higher than in the 2006 FIFA World Cup, and the average number of all used medications per player remained the same level as 4 years prior, with all its implications for the player's health. More efforts need to be undertaken worldwide in order to reduce the administration of medications in sports, through continuous education for players, starting from a young age, as well as for doctors and paramedics.